2022
DOI: 10.15361/2175-0106.2022v38n3p127-138
|View full text |Cite
|
Sign up to set email alerts
|

SAFETY OF ORAL DOXYCYCLINE TREATMENT IN NILE TILAPIA, Oreochromis niloticus

Abstract: This study aimed to evaluate the clinical safety of doxycycline treatment (Sandoz Pharmacetical Industry from Brazil Ltd.), administered orally incorporated into the feed of Nile tilapia, Oreochromis niloticus. For this purpose, 75 Nile tilapia (± 300g) from the same spawning were randomly distributed in 15 tanks (n=5), containing 100 L of water each, supplied with running water free from chlorine, to establish the following treatments: T0 (Control -not treated with doxycycline); T1, T2, T3 and T4 (treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Doxycycline and florfenicol are most commonly used veterinary antibiotics in China (Qian et al, 2021). Previous studies have demonstrated the clinical safety of oral treatment with doxycycline and florfenicol in fish aquaculture (Gaunt et al, 2013;Oliveira et al, 2022), and oral administration of doxycycline and florfenicol are effective in controlling mortality from enteric septicemia of channel catfish Ictalurus punctatus and edwardsiellasis of yellow catfish Pelteobagrus fulvidraco (Gaunt et al, 2013;Xu et al, 2021). In the present study, the DX2 isolate was highly susceptible to doxycycline and florfenicol.…”
Section: Discussionsupporting
confidence: 55%
“…Doxycycline and florfenicol are most commonly used veterinary antibiotics in China (Qian et al, 2021). Previous studies have demonstrated the clinical safety of oral treatment with doxycycline and florfenicol in fish aquaculture (Gaunt et al, 2013;Oliveira et al, 2022), and oral administration of doxycycline and florfenicol are effective in controlling mortality from enteric septicemia of channel catfish Ictalurus punctatus and edwardsiellasis of yellow catfish Pelteobagrus fulvidraco (Gaunt et al, 2013;Xu et al, 2021). In the present study, the DX2 isolate was highly susceptible to doxycycline and florfenicol.…”
Section: Discussionsupporting
confidence: 55%
“…these results agree with those found in the treatment of growing pigs by Harvey et al, (1995), where the administration of lincomycin did not result in significant alteration in hematological parameters. and Oliveira et al (2022) did not observe differences between hematological parameters in clinical safety studies in tilapia with zileuton and doxycycline, respectively. In contrast, Amer et al (2017) studied oral administration of lincomycin in rats, and they found a significant decrease in the number of erythrocytes, hemoglobin concentration and percentage of hematocrit at a daily dose of 500 mg/kg for 21 days.…”
Section: Discussionmentioning
confidence: 71%
“…The aquaculture sector is increasingly recognized for its essential contribution to global food security in the 21st century (FAO, 2022). Brazilian aquaculture has grown in recent years and is positioned as an important agribusiness sector (OLIVEIRA et al, 2022). However, intensive management practices with high population density and excessive fish handling result in stress, responsible for loss of performance, reproduction and resistance to pathogens (BELO et al, 2005;2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com o manual de Estratégias de Inclusão Produtiva para Pequenos Piscicultores da Embrapa (PEDROZA FILHO et al, 2014), a piscicultura de pequena escala ou familiar é frequentemente encorajada pelas autoridades governamentais, em que pequenos produtores rurais possam também incluir a criação de peixes entre suas atividades, porém o grande desafio seria como integrar este tipo de produção piscícola nos circuitos de comercialização. Porém, as criações intensivas com elevado adensamento populacional resultam em estresse dos animais, condição fisiológica que suprime os mecanismos de defesa dos peixes (CHARLIE-SILVA et al, 2020;COSTA et al, 2022), resultando em perdas econômicas significativas e necessitando de manejo sanitário das piscigranjas (OLIVEIRA et al, 2022) Existe uma tendência no mercado mundial pela busca de novas fontes de proteínas visando não só uma melhoria na dieta humana, mas também devido à grande pressão sobre as questões de No período de junho de 2021, foi realizada a análise dos possíveis impasses ambientais na propriedade e aos arredores, onde foi observada uma fonte de contaminantes que provinha da estrada paralela a propriedade, uma caçamba improvisada pelos moradores para depósito de lixo que estava localizada próximo ao acesso da propriedade. Além de não comportar a demanda de lixo dos Ao terminar a despesca, as instalações passaram por um período sem novo povoamento, chamado vazio sanitário (Figura 1).…”
Section: Introductionunclassified